RcgA and RcgR, two novel proteins involved in the conjugative transfer of rhizobial plasmids - Castellani, Lucas Gabriel (2022)
Rhizobia are Gram-negative bacteria that are able to establish a nitrogen-fixing symbiotic interaction with leguminous plants. Rhizobia genomes usually harbor several plasmids which can be transferred to other organisms by conjugation. Two main mechanisms of the regulation of rhizobial plasmid transfer have been described: quorum sensing (QS) and the rctA/rctB system. Nevertheless, new genes and molecules that modulate conjugative transfer have recently been described, demonstrating that new actors can tightly regulate the process. In this work, by means of bioinformatics tools and molecular biology approaches, two hypothetical genes are identified as playing key roles in conjugative transfer. These genes are located between conjugative genes of plasmid pRfaLPU83a from Rhizobium favelukesii LPU83, a plasmid that shows a conjugative transfer behavior depending on the genomic background. One of the two mentioned genes, rcgA, is essential for conjugation, while the other, rcgR, acts as an inhibitor of the process. In addition to introducing this new regulatory system, we show evidence of the functions of these genes in different genomic backgrounds and confirm that homologous proteins from non-closely related organisms have the same functions. These findings set up the basis for a new regulatory circuit of the conjugative transfer of plasmids.